An Assessment of the Army's Tactical Human Optimization, Rapid Rehabilitation and Reconditioning Program - Kelly, Terrence K. (RAND Corporation, 2013)
U.S. Army Special Operations Command asked RAND Arroyo Center to determine whether its Tactical Human Optimization, Rapid Rehabilitation and Reconditioning (THOR3) program is effectively utilizing the resources provided and to identify opportunities for improvement in the program's planning and implementation, staffing, leader development and education, facility and equipment requirements, and ability to support participating personnel.